Comparative Syntax of Secondary Academic Texts Across English and Ukrainian in Scientific Domains - Shcherbyna, Svitlana; Zaitseva, Nataliia; Puhach, Yuliia; Mozghova, Yaroslava; Dolynskyi, Ievgen (Editorial Salud, Ciencia y Tecnologia, 2025)
Introduction: Effective communication in modern science depends on many factors, including the syntactic organisation of academic texts, which allows for accurately conveying the essence of information, avoiding contradictory or double reading, and formulating ideas, concepts, and strategies. This article aims to analyse the syntactic features of school academic texts. Methods: To this end, the specific features of scientific communication of this type and the specifics of scientific thinking have been investigated. Results: The study's results will help improve the effectiveness of tools in scientific communication and deepen the methodological foundations of scientific discourse. The study analysed a large corpus of secondary scientific and academic texts (abstracts, reviews, abstracts, theses, and dissertations), describing and comparing the specifics of syntactic structures in Ukrainian and English; studied the peculiarities of writing secondary scientific texts; formulated specific recommendations and conducted a statistical analysis of the levels of comprehension of secondary scientific (academic) texts in the languages compared. It is established that secondary educational and scientific texts differ in the syntactic organisation of the text depending on the field of knowledge. Conclusions: Thus, the humanities are characterised by emotional syntax with rhetorical figures emphasising interpretation, while in technical texts, syntax is subject to strict logic and argumentation. The presence of descriptive constructions and emotional colouring characterises the syntax of scientific texts in the humanities. In contrast, technical fields are characterised by analytical sentence structure and syntax based on logical grammatical constructions.
Keywords: academic writing; scientific style; science; secondary education; syntactic structure; abstract